The Use of Wearable Technology in Monitoring Physical Activity and Training: A Systematic Review - Grzybowska, Dominika; Grzyb, Weronika; Idzik, Kamil; Jaślikowska, Adrianna; Kubicki, Adrian; Kurnik, Michał; Leśniak, Maria; Niderla, Natalia; Rachwał, Natalia; Rzeszutek, Jakub (Quality in Sport, 2026)
Introduction and purpose: Wearable technologies have become widely adopted tools for monitoring physical activity and optimizing athletic training, yet comprehensive evaluations of their accuracy and effectiveness remain fragmented. This systematic review synthesizes evidence on wearable technology in physical activity monitoring and sport-specific training. Materials and methods: A systematic search of PubMed, Embase, Web of Science, SPORTDiscus, and CENTRAL was conducted for studies published between 2015 and 2025, following PRISMA 2020 guidelines. Systematic reviews, meta-analyses, and primary validation studies were synthesized. Brief description of the state of knowledge: Step counting reached acceptable accuracy in leading consumer devices (mean absolute percentage error below 25%), and optical heart rate sensors performed well at rest and moderate intensity (MAPE below 10%). Energy expenditure estimation remained inaccurate across all devices (MAPE exceeding 30%). An umbrella review of 39 systematic reviews found that 79% of physical activity analyses favored wearable interventions. A meta-analysis of 23 trials involving 4,566 older adults reported significant improvements in daily step counts and physical activity time, whereas no significant effects were found in youth populations. Summary: Wearable devices offer acceptable accuracy for step counting and heart rate but not energy expenditure. Standardized validation protocols, algorithmic transparency, and long-term effectiveness studies are needed to maximize clinical and sporting utility.